A MESOPROTEROZOIC PALEOMAGNETIC POLE FROM THE YANGZHUANG FORMATION, NORTH CHINA AND ITS TECTONICS IMPLICATIONS - Pei J.; Zhao Y.; Yang Z. (My University, 2006)
A new paleomagnetic study has been carried out on Mesoproterozoic sediments in the Jixian area, North China. Detailed stepwise thermal demagnetization allows us to isolate three components from 141 oriented drill-core samples (14 sites). A low-temperature component (component A) identified from most of samples falls close to the present local earth field direction. A middle-temperature component (component B) is found only in 21 samples from four sites. The component B directions (after bedding correction) yield a paleopole position at 336.0°E, 10.2°N with A95 = 17.1°, which is close to the Lower Cambrian pole of the North China Block. Characteristic remanent directions with dual polarities obtained from high-temperature (component C) pass fold test. The directions yield a pole position at 190.4°E, 2.4°N with A95 = 11.9°. This result indicates that the North China Block was located in low latitude at ca. 1.35 Ga. Recently, several studies suggested that Laurentia, Baltica and Siberia were also situated at low latitudes from well dated paleopoles between ca. 1.5 and 1.25 Ga. This would imply that the North China Block, Laurentia and Baltica might drift together or close in the Mesoproterozoic. © 2006 Elsevier B.V. All rights reserved.
Keywords: MESOPROTEROZOIC; PALEOMAGNETIC; NORTH CHINA BLOCK; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская